Inspiracje Nietzscheańską myślą – Skrzydła Nietzschego Wojciecha Karpińskiego - Trygar, Barbara (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The aim of the article is to show the influence of Friedrich Nietzsche’s philosophy on literature. The category of borderland is primarily of cultural and symbolic significance. Wojciech Karpiński shows the way of Friedrich Nietzsche’s thought in discovering his eidos. The German philosopher lived a life between good and evil, joy and suffering, falling and rising upwards, and writers were inspired by this attitude.